2016
DOI: 10.1016/j.athoracsur.2016.04.054
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dominant Ventricle Morphology on Palliation Outcomes of Single Ventricle Anomalies

Abstract: At midterm follow-up, underlying cardiac anomaly and patient characteristics affect single ventricle palliation outcomes more than dominant ventricular morphology. As right ventricle and associated tricuspid valve failure might occur at late stages, the impact of dominant ventricular morphology on long-term outcomes requires further assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…Univariable Analysis of Death or Heart Transplantation After Surgery in Infants With Double Inlet Left Ventricle single ventricle palliation outcomes in patients with left dominant ventricle morphology, others have not shown significant difference at midterm follow-up[11,[18][19][20][21][22][23]. At our institution, we have demonstrated that patients' characteristics and underlying single ventricle anomaly were more associated with outcomes than dominant ventricle morphology.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Univariable Analysis of Death or Heart Transplantation After Surgery in Infants With Double Inlet Left Ventricle single ventricle palliation outcomes in patients with left dominant ventricle morphology, others have not shown significant difference at midterm follow-up[11,[18][19][20][21][22][23]. At our institution, we have demonstrated that patients' characteristics and underlying single ventricle anomaly were more associated with outcomes than dominant ventricle morphology.…”
mentioning
confidence: 85%
“…There are several differences between the left and right heart structures involving the ventricles, atrioventricular valves, and the coronary supply that make the right ventricle and tricuspid valve less equipped to support the systemic circulation long term. The available reports from the literature vary, and although some have demonstrated [21]. Moreover, palliation outcomes of patients with atrial isomerism and heterotaxy syndrome were related more to associated cardiac findings than dominant ventricle morphology [24].…”
Section: Commentmentioning
confidence: 99%
“…[6][7][8][9] Nonetheless, previous work has suggested tricuspid regurgitation is the single, largest, echocardiographic predictor of stage 2 failure. Historical risk factors include low weight at the time of stage 2 palliation, history of a genetic syndrome, and requirement of extracorporeal support or renal dialysis during stage 2 palliation hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Historical risk factors include low weight at the time of stage 2 palliation, history of a genetic syndrome, and requirement of extracorporeal support or renal dialysis during stage 2 palliation hospitalization. [6][7][8][9] Nonetheless, previous work has suggested tricuspid regurgitation is the single, largest, echocardiographic predictor of stage 2 failure. 10,11 Yet, echocardiographic measurement of right ventricular function as an independent variable to predict the success of stage 2 palliation in terms of both morbidity and mortality, is yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are limited studies investigating the influence of ventricle dominancy in this issue. Moreover, some authors indicate that recent progress in intensive care unit (ICU), developed technologies, and improved patient management lead to enhance outcomes in all stages, especially in hypoplastic left heart syndrome; therefore, such results might be associated with underlying cardiac morphology rather than the ventricle dominancy (9) . Within this study, we aimed to evaluate our single institute experience in patients to whom the Fontan procedure was performed; furthermore, to assess the effects of ventricle dominancy on perioperative and postoperative findings, comorbidities, and survival.…”
Section: Research Article Introductionmentioning
confidence: 99%